Pengaruh Moral, Frekuensi Pelatihan Pelaporan Perpajakan, dan Norma Subjektif terhadap Kepatuhan Pajak Melalui Pemahaman Akuntansi pada Pelaku Usaha Mikro KPP Pratama Cilegon - Dadan Ramdhani; Wahyu Yulianto Wibowo; Popong Suryani; Bima Prabowo (Universitas Matana, 2019)
The purpose of this study was to examine the effect of morale, frequency of tax reporting training, and subjective norms againts tax compliance through understanding accounting. This research was carried out at Kantor Pelayanan Pajak (KPP) Pratama Cilegon. This study uses primary data obtained from the questionnaire. The sample used in this study is a Micro, Small and Medium Enterprises Taxpayers registered at KPP Pratama Cilegon. The sampling technique used is purposive sampling. 145 questionnaires were distributed, and 145 questionnaires were returned. Data were analyzed using Statistical Product and Service Solution (SPSS) version 23. The results of this study indicate that morale, subjective norms and understanding of accounting have a significant effect on tax compliance, while the frequency of tax reporting training does not affect tax compliance. Morale and subjective norms do not affect the understanding of accounting, while the frequency of tax reporting training influences the understanding of accounting. Morale, frequency of tax reporting training, and subjective norms have no effect againts tax compliance through understanding accounting.